Pediatric imaging - Gunderman, Richard B.; Delaney, Lisa R. (RadCases, 2010)
"Pediatric radiology is a special field. It is distinguished from most other radiologic disciplines by the fact that it addresses all of the organ systems and imaging modalities. Moreover, it focuses on the most formative and resilient stages of life, from infancy to adolescence. The patients it serves are in some respects the most vulnerable and precious of all. Like other pediatric fields, it is populated by people of special optimism and dedication, and pediatric radiologists typically enjoy relationships of high mutual respect and gratitude with patients, families, and referring health professionals. Studying pediatric radiology is a special privilege, offering opportunities to explore the anatomy, physiology, and pathology of the developing human, and to put to work for our patients some of the most remarkable diagnostic advances in the recent history of medicine. We feel blessed to count ourselves among the long line of physicians who have practiced this craft, and we offer these cases with the hope that they will enrich the quality of care of infants, children, and adolescents for years to come"--Provided by publisher.